Bio-oil Production from Pyrolysis of Palm Oil Wastes - Nurul Fatin Shazwani, Suhaimi (2012)
Energy demand is increasing rapidly because of the growth of population and industrialization. However, the conventional energy source is depleting. Biomass is abundant but inefficiently utilized. Pyrolysis of biomass is the one of the alternative ways to encounter this problem. The products of pyrolysis are bio-oil, char and gas. In this research, the production of bio oil from the pyrolysis of palm oil fiber (POF) and palm oil empty fruit bunch (EFB) were studied using a small lab scale pyrolysis unit. The objectives of this research are to investigate the effect of sample size and produce bio oil from EFB and POF. Preliminary analysis was conducted using thermo gravimetric analyzer (TGA) to determine the volatility, ash residue and moisture content. From the result of the TGA, it is found that EFB contain more volatile matter in comparison to POF. It can also be concluded that EFB might produced more bio oil than POF. Meanwhile, the effect of sample size towards the yield was also studied. The sample size was varied between < 0.63 mm, 0.63-2 mm and 2-4 mm. The best size, which is < 0.63 mm, was pyrolysed in a reactor at constant temperature of 500 oC. The general characteristic of the product was investigated by the determination of functional groups present in bio oil using Fourier Transform Infrared spectrometer (FTIR). From the analysis, it is shown that bio oil contains complex compounds mostly functional groups of phenol, alcohol, ketones, aldehydes, carboxylic acid and carbonic structure. Physical properties of the bio oil such as pH and viscosity were also investigated. From the result, the pH for the bio oil is 3.99 and the viscosity value is 34 cP.